Comparative Study of Traditional Chinese Medicine and Indian Traditional Medicine from the Perspective of International Development - CHEN Ying, ZHOU Shuduo, YANG Jian, HU Yunxuan, FENG Xiangning, XU Ming (Zhongguo quanke yixue)
Traditional Chinese medicine (TCM) is an important part of Chinese traditional culture. It's also an important health resource, economic resource, technological resource, cultural resource and ecological resource in our country. The international development of TCM is an important part of the inheritance and innovation of TCM. In the global traditional medicine system, Indian traditional medicine is the most influential. Development status, international development strategies and impact of Indian traditional medicine are greatly comparable with those of TCM. From the perspective of international development, this paper compared TCM and Indian traditional medicine from seven aspects: service delivery, health workforce, production capacity of traditional medicines, financial allocation for health system and health insurance policy, health governance, product export situation and target markets, international development and influence. It aimed to learn from the successful experience of the international development of Indian traditional medicine, and provide reference for the international development of TCM. In order to actively promote the international development of TCM, make important contributions to deepening the cultural identity of TCM overseas and promote the participation of TCM in global health governance.